Cognition and Evolution of Movement Disorders of FOXG1-Related Syndrome - Wong, Lee-Chin; Wu, Yen-Tzu; Hsu, Chia-Jui; Weng, Wen-Chin; Tsai, Wen-Che; Lee, Wang-Tso (Frontiers in Neurology, 2019)
FOXG1-related syndrome is a rare neurodevelopmental encephalopathy characterized by early onset hyperkinetic movement disorders, absent language, autistic features, epilepsy, and severe cognitive impairment. However, detailed evaluation of cognition and evolution of movement disorders overtime are not clearly described before. In this study, we performed whole-exome sequencing in a cohort with unknown severe encephalopathy and movement disorders, with/without autistic behaviors. We identified FOXG1 mutations in three patients. Two of them had novel mutations that was not described before. The neuropsychological test by Mullen Scales of Early Learning (MSEL) showed severe psychomotor impairments in all patients. There were uneven cognitive abilities in terms of verbal and nonverbal cognitive domains in all of them, with approximately 2 months differences. The gross motor and expressive language were more severely affected than the other domains in all the patients. All individuals had early onset hyperkinetic movement disorders. The movement disorders in one of our patients changed from predominantly hyperkinetic in early childhood to more hypokinetic in adolescence with the development of dystonia. To the best of our knowledge, this evolution had never been described before. In conclusion, individuals with FOXG1-related syndrome may show clinical progression from hyperkinetic to hypokinetic features over time. There were also uneven cognitive abilities in verbal and nonverbal cognitive domains. FOXG1 mutation should be considered in individuals with a history of hyperkinetic movements, microcephaly, and uneven cognitive abilities with characteristic brain images.